Applications of MALDI Mass Spectrometry in Clinical Chemistry. (6th January 2020) - Duncan, Mark W; Nedelkov, Dobrin; Walsh, Ryan; Hattan, Stephen J
Abstract: BACKGROUND: MALDI-TOF mass spectrometry (MS) is set to make inroads into clinical chemistry because it offers advantages over other analytical platforms. These advantages include low acquisition and operating costs, ease of use, ruggedness, and high throughput. When coupled with innovative front-end strategies and applied to important clinical problems, it can deliver rapid, sensitive, and cost-effective assays. CONTENT: This review describes the general principles of MALDI-TOF MS, highlights the unique features of the platform, and discusses some practical methods based upon it. There is substantial potential for MALDI-TOF MS to make further inroads into clinical chemistry because of the selectivity of mass detection and its ability to independently quantify proteoforms. SUMMARY: MALDI-TOF MS has already transformed the practice of clinical microbiology and this review illustrates how and why it is now set to play an increasingly important role in in vitro diagnostics in particular, and clinical chemistry in general.